One-step method for the isolation of α-lactalbumin and β-lactoglobulin from cow's milk while preserving their antigenicity. Issue 4 (3rd April 2017) - Mao, Xue; Zhang, Guo-Fang; Li, Chun; Zhao, Yu-Cai; Liu, Yang; Wang, Ting-Ting; Duan, Chun-Ying; Wang, Jing-Ying; Liu, Li-Bo
ABSTRACT: Milk is a highly nutritional food, and separation of major allergens from milk has become important to people who are allergic. The aim of this study was to establish a simple and repeatable method for the isolation of α-lactalbumin and β-lactoglobulin from cow's milk while preserving their antigenicity. Fractions of α-lactalbumin and β-lactoglobulin were salted-out using 50% ammonium sulfate from whey that was collected from cow's milk after pH adjustment and then purified by anion-exchange chromatography with diethylaminoethyl-Sepharose Fast Flow. The antigenicity of the purified proteins was evaluated by indirect competitive enzyme-linked immunosorbent assay. The results showed that the purities of the α-lactalbumin and β-lactoglobulin collected were 84.85 and 94.91% and the cross-reactivities of the purified proteins were 93.2 and 95.4%, respectively. Therefore, this simple and efficient strategy consisting of a one-step process for α-lactalbumin and β-lactoglobulin is suitable for purifying the major allergens in cow's milk. In addition, a scientific experimental basis for the preparation of non-allergenic milk was also offered in this study.